Paperbark and pinard: A historical account of maternity care in one remote Australian Aboriginal town - Ireland, S.; Belton, S.; McGrath, A.; Saggers, Sherry; Narjic, C. (Elsevier, 2015)
Background and aim: Maternity care in remote areas of the Australian Northern Territory is restricted to antenatal and postnatal care only, with women routinely evacuated to give birth in hospital. Using one remote Aboriginal community as a case study, our aim with this research was to document and explore the major changes to the provision of remote maternity care over the period spanning pre-European colonisation to 1996. Methods: Our research methods included historical ethnographic fieldwork (2007-2013); interviews with Aboriginal women, Aboriginal health workers, religious and non-religious non-Aboriginal health workers and past residents; and archival review of historical documents. Findings: We identified four distinct eras of maternity care. Maternity care staffed by nuns who were trained in nursing and midwifery serviced childbirth in the local community. Support for community childbirth was incrementally withdrawn over a period, until the government eventually assumed responsibility for all health care. Conclusions: The introduction of Western maternity care colonised Aboriginal birth practices and midwifery practice. Historical population statistics suggest that access to local Western maternity care may have contributed to a significant population increase. Despite population growth and higher demand for maternity services, local maternity services declined significantly. The rationale for removing childbirth services from the community was never explicitly addressed in any known written policy directive. Declining maternity services led to the de-skilling of many Aboriginal health workers and the significant community loss of future career pathways for Aboriginal midwives. This has contributed to the current status quo, with very few female Aboriginal health workers actively providing remote maternity care.